Totals of the European Bison year 2009 in Ukraine - Ivan Parnikoza (Праці Теріологічної школи, 2010)
The Ukrainian Eco-NGO Coalition, Theriological School and Ministry for Environmental Protection proclaimed the year 2009 the Bison Year in Ukraine. The campaign allowed to evaluate the bison population and to publicize widely the minatory state of the species and the possible ways to save the Ukrainian population.